Ameliorative effects of crocin on paraquat-induced oxidative stress in testis of adult mice: An experimental study - Sadat Kamali, Fahime (Int J Reprod Biomed, 2019)
BACKGROUND: Paraquat (PQ), as a pyridine compound, is widely used worldwide to control annual weeds. The oxidative stress caused by PQ can cause deleterious changes in the testicular tissue. OBJECTIVE: An investigation on the protective effects of Crocin (CCN) against PQ-induced oxidative damages and apoptotic indices in testicular tissue. MATERIALS AND METHODS: Twenty-eight adult male albino mice (20-25 gr) were divided into four groups (n = 7/each). The control group received 0.1 ml/day of normal saline by intraperitoneal injection (IP); sham-control group received PQ 5 mg/kg/day, IP, and the experimental groups received PQ (CCN+PQ) and CCN-sole (200 mg/kg/day, IP), respectively, for 35 continuous days. At the end of the treatment period, the testes were dissected out and used for biochemical, molecular, and histological analyses. The expressions of tumor suppressor p53, B-cell lymphoma 2 (bcl-2), and caspase-3 were considered as hallmark factors of mitochondria-dependent apoptosis. Moreover, the testicular superoxide dismutase (SOD) and malondialdehyde (MDA) were evaluated as key biomarkers for oxidative stress. RESULTS: The PQ significantly (p [Formula: see text] 0.02, p [Formula: see text] 0.01) diminished the spermatogenesis indices and SOD, increased MDA levels, and enhanced the apoptosis-related gene expression. However, the co-administration of CCN and PQ significantly (p [Formula: see text] 0.01, p [Formula: see text] 0.01, p [Formula: see text] 0.02) ameliorated the spermatogenesis ratio, upregulated the SOD level as well as bcl-2 expression, and reduced the MDA content and apoptosis vs the PQ-sole group. CONCLUSION: This study showed that the antioxidant properties of CCN enable to ameliorate the PQ-induced destructive effects by upregulating the testicular structure, antioxidant and apoptotic status.